Digital Skills: Social Disparities and the Impact of Early Mentoring - Fabian Kosse; Tim Leffler; Arna Woemmel (CESifo GmbH, 2024)
We investigate social disparities in digital skills, focusing on both actual proficiency levels and confidence in these skills. Drawing on a representative sample from Germany, we first demonstrate that both dimensions strongly predict labor market success. We then use this sample to identify gender and socioeconomic disparities in levels and confidence. Finally, using a long-run RCT panel framework with young adults, we confirm these disparities and provide causal evidence on the effects of enhancing the social environment in childhood. Assigning elementary school-aged children to a mentoring program persistently reduces socioeconomic gaps in confidence related to digital skills, but it does not affect the level of digital skills.
Keywords: C93; D63; I24; J24; O33; 330; digital skills; technological transformation; inequality; early childhood mentoring